2017
DOI: 10.1007/s10113-017-1202-9
|View full text |Cite
|
Sign up to set email alerts
|

Generality of relationships between leaf pigment contents and spectral vegetation indices in Mallorca (Spain)

Abstract: Vegetation indices are calculated from reflectance data of discrete spectral bands. The reflectance signal in the visible spectral range is dominated by the optical properties of photosynthetic pigments in plant leaves. Numerous spectral indices have been proposed for the estimation of leaf pigment contents, but the efficacy of different indices for prediction of pigment content and composition for species-rich communities is unknown. Assessing the ability of different vegetation indices to predict leaf pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 69 publications
3
24
0
2
Order By: Relevance
“…These inter-correlations must be considered when interpreting the relationships between forest parameters and spectral characteristics. In a leaf level study [17], we found that the simple ratio of reflectances at 751 nm and 736 nm was the best predictor of leaf chlorophyll content. To assess how such long wavelengths would operate at canopy level, we calculated the same index in our current study.…”
Section: Correlation Between Single Band Reflectance Factors and Specmentioning
confidence: 88%
See 2 more Smart Citations
“…These inter-correlations must be considered when interpreting the relationships between forest parameters and spectral characteristics. In a leaf level study [17], we found that the simple ratio of reflectances at 751 nm and 736 nm was the best predictor of leaf chlorophyll content. To assess how such long wavelengths would operate at canopy level, we calculated the same index in our current study.…”
Section: Correlation Between Single Band Reflectance Factors and Specmentioning
confidence: 88%
“…Using spectral bands at 736 nm and 751 nm wavelengths suggested by Hallik et al [17], we found that SR (Equation (4)) and NDVI (Equation (5)) forms were almost linearly related to each other ( Figure 4C) and therefore we used only a single formulation of Equation (4)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control and drought groups for both maize hybrids showed less reflectance in the 500-700 nm (VIS) range compared to that of RDX. This range represents chlorophyll a and b, carotenoids, and accessory pigments and is used as a non-destructive method to derive pigment concentrations [36]. RDX has been shown to cause reductions in chlorophyll concentrations [13,14] which can be interpreted as increases in reflectance in VIS wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Hallik et al (2017) focuses on relationships between leaf pigment contents and spectral vegetation indices using a chemically and structurally large dataset sampled in Mallorca, Balearic Islands. The dataset covers plants from mesic environments as well as from highly stressed environments supporting plants with unique leaf optical properties.…”
Section: This Special Issuementioning
confidence: 99%